Application Design “Xanthe Original Distro” Web Based to Increase Sales Value - Satria Hidayahtullah; Arif Senja Fitrani (Procedia of Engineering and Life Science, 2022)
Xanthe Original distributions have quite a number of buyers or members, in this case, the main focus that will be evaluated is how to process online and offline sales of original Xanthe products. Online sales of original Xanthe products are still required to contact the original Xanthe distribution via WhatsApp to ask for stock, product details, product prices, and product delivery costs, so members or buyers must wait first until the distribution party replies to the WhatsApp chat, while in offline sales Xanthe products originals are required to come to the original Xanthe distro, and the problem that often occurs when buyers come directly to the distribution is that the product they want to buy is out of stock. The purpose of designing this application is to produce an effective and efficient sales application on the Xanthe Original distribution. The research used in completing this sales application is observation, interviews, and documentation carried out at the Xanthe Original Distro Sidoarjo. This sales application is made using the PHP Native programming language and MySQL as the database. The results of the research on this sales application are that the distribution party can manage goods data, category data, expedition data, member data, and computerized sales data. This application is expected to make it easier for members to buy original Xanthe products because product orders and product payments are made online, and there is no need to come to the store.